CORPORATE TAX COMPLIANCE AND MEDIATING ROLE OF PERSONAL TAX COMPLIANCE AMONG MALAYSIAN IN-HOUSE TAX PROFESSIONALS - Sritharan, Nivakan; Salawati, Sahari; Sharon Cheuk, Choy Sheung; Ahmad Syubaili, Mohamed (UUM Press, 2023)
Studies relating to tax compliance disclose that there is much likelihood of the corporate tax compliance behaviour getting influenced by the tax compliance behaviour of the in-house tax professionals. However, no studies have investigated the nexus between the personal tax compliance and the corporate tax compliance so far. Therefore, this study aims at investigating the link between the above two tax compliance behaviours and the mediating effect of the personal tax compliance behaviour of the in-house tax professionals on their corporate tax compliance behaviour. A sequential explanatory design is chosen to collect data from 392 in-house tax professionals through a survey questionnaire, and the findings obtained from the survey are supported further by the supplementary findings made by nine (9) tax experts from the tax authority, tax agency, and tax scholars of the institutions in Malaysia. Structural equation modelling is used to analyse the data taken from the findings that reveal that the factors that contribute to the tax compliance behaviour have strong influence on the personal tax compliance of the in-house tax professionals. Interestingly, their tax compliance behaviour strongly influences their corporate tax compliance as well. Further, the bootstrapping test reveals that personal tax compliance behaviour has a significant indirect effect on the corporate tax compliance. The empirical findings give a clue to the tax authorities to identify the root cause for the corporate tax non-compliance by investigating the decision makers’ tax compliance pattern. The researchers of the future studies are encouraged to follow the same method of data collection, along with the sequential explanatory design, and to consider the moderation effect of the financial constraints on the tax compliance behaviour.